2020
DOI: 10.1177/1075547019899408
|View full text |Cite
|
Sign up to set email alerts
|

Climate Engineering as a Communication Challenge: Contested Notions of Responsibility Across Expert Arenas of Science and Policy

Abstract: Climate engineering (CE) is often said to bring about significant opportunities as well as risks. The pursuit of CE measures can be framed as either responsible or irresponsible, resulting in contentious and ambiguous communication. This article starts out from a notion of responsibility regarding subjects, objects, norms, and authorities. It will identify and analyze discursive patterns of responsibility across six expert arenas and provide a comparative mapping of these patterns. Better understanding controv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The responsibility of care rationale also adds a new discursive model of responsibility to those previously identified in the CE debate (Matzner & Barben, 2020). In contrast to the 'responsibility to manage the planet' pattern identified by Matzner & Barben in the science/policy sphere of the debate, which lacks an underpinning norm and an entity to which humanity is accountable, the relational responsibility model present in religious discourse is based on the ethic of care and posits that humanity is responsible to both themselves (as part of a socio-ecological whole), and to God (as embodied in all creation on Earth), to care for the Earth system (see Figure 2).…”
Section: Rationales: Care Balance and Humility In Ce Governancementioning
confidence: 97%
See 1 more Smart Citation
“…The responsibility of care rationale also adds a new discursive model of responsibility to those previously identified in the CE debate (Matzner & Barben, 2020). In contrast to the 'responsibility to manage the planet' pattern identified by Matzner & Barben in the science/policy sphere of the debate, which lacks an underpinning norm and an entity to which humanity is accountable, the relational responsibility model present in religious discourse is based on the ethic of care and posits that humanity is responsible to both themselves (as part of a socio-ecological whole), and to God (as embodied in all creation on Earth), to care for the Earth system (see Figure 2).…”
Section: Rationales: Care Balance and Humility In Ce Governancementioning
confidence: 97%
“…Secondly, the rationales of responsible care (of and by socio-ecological systems), balance, and humility underpinning this governmentality reinforce a relational perspective that may be central to developing more holistic, non-hierarchical and non-linear understandings of human responsibility and agency in global environmental governance. Specifically, the SEC may offer a new model of human responsibility for deliberate interventions into socio-ecological systems that goes beyond the technocratic model of responsibility for 'planetary management' previously identified in the CE governance debate (Matzner & Barben, 2020).…”
Section: Speaker Positions: Roles For Religious Knowledge Reproducersmentioning
confidence: 99%
“…The responsibility of care rationale also adds a new discursive model of responsibility to those previously identified in the CE debate (Matzner and Barben, 2020). In contrast to the 'responsibility to manage the planet' pattern identified by Matzner & Barben in the science/ policy sphere of the debate, which lacks an underpinning norm and an entity to which humanity is accountable, the relational responsibility model present in religious discourse is based on the ethic of care and posits that humanity is responsible to both themselves (as part of a socio-ecological whole), and to God (as embodied in all creation on Earth), to care for the Earth system (see Figure 7).…”
Section: Rationales: Care Balance and Humility In Ce Governancementioning
confidence: 97%
“…Biermann and Möller, 2019, Gupta and Möller, 2018, Möller, 2020. This research has demonstrated how discussions on the feasibility and responsibility of various CE approaches have prioritised scientific and technical knowledge types (Low and Schäfer, 2020, Matzner and Barben, 2018, Matzner and Barben, 2020. This is seen as particularly problematic in the Global South, where memories of broken promises mean that NETs may be seen as means for the Global North to avoid their responsibilities to reduce emissions (Cox et al, 2020a, Möller, 2020.…”
Section: The Role Of Discoursementioning
confidence: 98%
See 1 more Smart Citation